2017
DOI: 10.1371/journal.pone.0170416
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Increased Gastric Juice Acidity and Sliding Hiatal Hernia Development in Humans

Abstract: ObjectivesSeveral clinical factors; overweight, male gender and increasing age, have been implicated as the etiology of hiatal hernia. Esophageal shortening due to acid perfusion in the lower esophagus has been suggested as the etiological mechanism. However, little is known about the correlation between gastric acidity and sliding hiatus hernia formation. This study examined whether increased gastric acid secretion is associated with an endoscopic diagnosis of hiatal hernia.MethodsA total of 286 consecutive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Collected gastric juice was categorized into two groups by acid level of pH 3, since previous studies observed below pH 3 as normal gastric acidity range. 3 , 25 In this study, we found that H. pylori infection was significantly associated with gastric acidity. In other words, pH <3 group showed 21.4% of H. pylori infection rate, but pH ≥3 group showed much higher infection rate (61.1%, p=0.007).…”
Section: Discussionmentioning
confidence: 53%
“…Collected gastric juice was categorized into two groups by acid level of pH 3, since previous studies observed below pH 3 as normal gastric acidity range. 3 , 25 In this study, we found that H. pylori infection was significantly associated with gastric acidity. In other words, pH <3 group showed 21.4% of H. pylori infection rate, but pH ≥3 group showed much higher infection rate (61.1%, p=0.007).…”
Section: Discussionmentioning
confidence: 53%
“…19 Interestingly, females were more likely to undergo this operation than males, consistent with the previous series by Bjelovic et al 27 However, the literature concerning risk factors for PEH hernias cites male gender as a risk factor for developing a PEH. 5,6 Reasons for this outcome are not readily apparent, but may include: females are more likely to be diagnosed than males; that the incidence of PEH is unrelated to the need for PEH surgical intervention; or there is interventional bias.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Increasing age (>50 years) and being overweight (body mass index >25 kg/m 2 ) are the most common risk factors for HH formation. [5][6][7][8][9] A study conducted in 2013 by Che et al found that 40% of the morbidly obese patients had a HH, 10 while subsequent studies have shown that HH prevalence is associated with obesity prevalence and increasing age. [5][6][7][8][9] A study conducted in 2013 by Che et al found that 40% of the morbidly obese patients had a HH, 10 while subsequent studies have shown that HH prevalence is associated with obesity prevalence and increasing age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kishikawa H, Kimura K, Ito A, Arahata K, Takarabe S, Kaida S, et al (2017) Correction: Association between Increased Gastric Juice Acidity and Sliding Hiatal Hernia Development in Humans. PLoS ONE 12(2): e0172375.…”
mentioning
confidence: 99%